A random survey of the prevalence of falsified and substandard antibiotics in the Lao PDR - Tabernero, P; Swamidoss, I; Mayxay, M; Khanthavong, M; Phonlavong, C; Vilayhong, C; Sichanh, C; Sengaloundeth, S; Green, MD; Newton, PN (Oxford University Press, 2022)
Objectives In 2012, a stratified random survey, using mystery shoppers, was conducted to investigate the availability and quality of antibiotics sold to patients in the private sector in five southern provinces of the Lao People’s Democratic Republic (Laos). Methods A total of 147 outlets were sampled in 10 districts. The active pharmaceutical ingredient (API) content measurements for 909 samples, including nine APIs (amoxicillin, ampicillin, ceftriaxone, ciprofloxacin, doxycycline, ofloxacin, sulfamethoxazole, tetracycline and trimethoprim), were determined using HPLC. Results All the analysed samples contained the stated API and we found no evidence for falsification. All except one sample had all the units tested with %API values between 75% and 125% of the content stated on the label. However, we identified the presence of substandard antibiotics: 19.6% (201/1025) of samples had their units outside the 90%–110% content of the label claim and 18.3% (188/1025) of the samples had units outside the International Pharmacopoeia/United States Pharmacopoeia assay (percentage of label claim) specifications. Trimethoprim had a high number of samples [51.6% (64)] with units below the limit range, followed by ceftriaxone [42.9% (3)] and sulfamethoxazole [34.7% (43)]. Doxycycline, ofloxacin and ciprofloxacin had the highest number of samples with high API content: 43.7% (38), 14.7% (10) and 11.8% (2), respectively. Significant differences in %API were found between stated countries of manufacture and stated manufacturers. Conclusions With the global threat of antimicrobial resistance on patient outcomes, greater understanding of the role of poor-quality antibiotics is needed. Substandard antibiotics will have reduced therapeutic efficacy, impacting public health and control of bacterial infections.